Analisis Pendayagunaan Tenaga Rekam Medis Di Puskesmas Kota Padang - Oktamianiza Oktamianiza; Devid Leonard (Indonesian of Health Information Management Journal (INOHIM), 2019)
AbstractUtilization of health workers is an effort to equalize, utilize and develop health workers. The initial survey was conducted at five puskesmas in Padang, namely Pemancungan Puskesmas, Padang Pasir Puskesmas, Air Tawar Puskesmas, Rawang Puskesmas and Ambacang Puskesmas. Researchers found that there are still human health (HR) resources that manage medical record units instead of skilled workers graduating from diploma three (D-III) medical records. Puskesmas which have skilled medical records have not been utilized properly due to uneven distribution. The purpose of this study was to analyze the utilization of medical records personnel in the Padang City Health Center. The study was conducted from 18 May to 3 June 2018. This type of qualitative research was a case study approach. There were 11 informants in the study. The study was conducted with in-depth interviews using in-depth interview guidelines and observation. Data processing and analysis consists of transcription, reduction, coding and categorization. The sampling technique is purposive sampling that is people who know, are involved in the topic of the research being conducted. The results of the analysis showed that the distribution of medical recorders and health information was not evenly distributed, the job description was not in accordance with Permenpan No.30 of 2013, there were still medical record personnel who did not have a medical record education background, namely graduates from high school and lack of training or educational development of the record workers. medical and non-medical records. The City Health Office and the Puskesmas should encourage the distribution of medical record personnel through the Regional Public Service Board (BLUD) by specializing in medical background education. Workers with a high school education background can continue their education through the Past Learning Recognition (RPL) program.Keywords: medical record, utilization, first level health facilities (FKTP)AbstrakPendayagunaan tenaga kesehatan adalah upaya pemerataan, pemanfaatan dan pengembangan tenaga kesehatan. Survei awal dilakukan pada lima puskesmas yang ada di Padang yaitu Puskesmas Pemancungan, Puskesmas Padang Pasir, Puskesmas Air Tawar, Puskesmas Rawang dan Puskesmas Ambacang. Peneliti menemukan masih ada sumber daya manusia (SDM) kesehatan yang mengelola unit rekam medis bukan tenaga terampil lulusan dari diploma tiga (D-III) rekam medis. Puskesmas yang sudah ada tenaga terampil rekam medis belum didayagunakan secara baik karena distribusi yang belum merata. Tujuan penelitian ini untuk menganalisa pendayagunaan tenaga rekam medis di Puskesmas Kota Padang. Penelitian dilaksanakan pada tanggal 18 Mei - 3 Juni 2018. Jenis penelitian kualitatif dengan pendekatan case study. Informan dalam penelitian berjumlah 11 orang. Penelitian dilakukan dengan indepth interview menggunakan pedoman wawancara mendalam dan observasi. Pengolahan dan analisa data terdiri dari transkripsi, reduksi, koding dan kategorisasi. Teknik pengambilan sampel yaitu purposive sampling yaitu orang yang mengetahui, terlibat terkait topik penelitian yang dilakukan. Hasil analisis didapatkan distribusi tenaga perekam medis dan infomasi kesehatan belum merata, uraian tugas tidak sesuai dengan Permenpan No.30 Tahun 2013, masih ditemukan tenaga rekam medis yang tidak berlatar belakang pendidikan rekam medis yaitu tamatan dari SMA dan minimnya pelatihan atau pengembangan pendidikan terhadap tenaga rekam medis dan non rekam medis. Dinas Kesehatan Kota dan Puskesmas sebaiknya mendorong pemerataan distribusi tenaga rekam medis melalui Badan Layanan Umum Daerah (BLUD) dengan mengkhususkan penerimaan yang berlatar belakang pendidikan rekam medis. Tenaga yang berlatar pendidikan SMA dapat melanjutkan pendidikan melalui program Rekognisi Pembelajaran Lampau (RPL).Kata Kunci: rekam medis, pendayagunaan fasilitas kesehatan tingkat pertama (FKTP)